PENGARUH LOVE OF MONEY, PERILAKU ETIS MAHASISWA DAN KOMITMEN ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSIDENGAN GENDER SEBAGAI VARIABEL PEMODERASI - Lukita Tripermata (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aimed to analyze whether there is influence between the love of money, ethical behavior, and organizational commitment to the tendency of accounting fraud by gender moderation. This research basically developed with quantitative approach. The study population includes all students Tier 1 Department of Accounting and Management Faculty of Economics at the University of Indo Global Mandiri Palembang. Samples were taken using the method of data collection is called purposive sampling. The samples used were 81 participants from 86 participants overall. Data collection techniques used is through questionnaires. Data analysis techniques were analyzed with descriptive statistics, classical assumption (normality test, multicollinearity, heteroskedasitisitas), t-test and ANOVA.Results showed hypothesis 1 is accepted because there is a positive and significant relationship, then there is an interaction Love of Money (LOM) against the tendency of Cheating Accounting (KKA). Testing the hypothesis is accepted because there are two positive and significant relationship between the perception of ethical (PE) by gender on Accounting Fraud Trends (KKA). While the hypothesis 3 are positive and significant relationship Organizational Commitment (KO) against the tendency of Cheating Accounting (KKA). Thus, the third hypothesis is accepted. Keywords: Love of Money, ethical behavior, organizational commitment, gender